A subtour-free set-sequencing algorithm based computer software for solving the machine set-up problem (2007)
The machine set-up problem (MSP) is that of determining an optimal sequence that a set of N operations will be performed by a general- purpose facility. In order to minimize tile total cost/time of re-setting the facility. Though the MSP is experienced in many small scale industrial situations many of the existing algorithm are programmed to run on super computers or massively parallel computer processors which are often not available for small scale industrial environment in developing economies. In this study a Subtour-free Set Sequencing Algorithm based software for solving real life medium size machine set-up problem on personal computers was developed and tested The computational time curve exhibited a polynomial growth for the range of problems solved and the solution system was shown to be practicable